Primary neuroendocrine carcinoma of the breast - Akhtar Kafil; Zaheer Sufian; Ahmad S; Hassan M (Indian Journal of Pathology and Microbiology, 2009)
Primary neuroendocrine carcinoma of the breast is rare-only about 30 cases have been reported in literature. Immunohistochemical examination showing expression of chromogranin and/or synaptophysin confirms evidence of neuroendocrine differentiation. Usually foci of neuroendocrine differentiation can be seen in breast carcinoma and are reported to be present in about 2-5% of breast cancer cases. Here, we report a case of breast carcinoma in which most of the areas studied on the tissue section showed neuroendocrine differentiation.